Acceptability and perceived feasibility of strategies to increase public transport use for physical activity gain – A mixed methods study. (20th September 2019) - Sharman, Melanie J.; Lyth, Anna; Jose, Kim A.; Ragaini, Bruna Silva; Blizzard, Leigh; Johnston, Fay H.; Peterson, Corey; Palmer, Andrew J.; Cleland, Verity J.
Abstract: Issue addressed: Public transport (PT) users typically accumulate more physical activity (PA) than motor vehicle users. This mixed methods study aimed to determine acceptability and perceived effectiveness of strategies to increase bus use for PA gain in a regional Australian setting. Methods: In a 2017 online survey, Tasmanian adults (n = 1091) rated the likelihood of increasing their bus use according to ten hypothetical strategies (fare‐, incentives‐, information‐ or infrastructure‐based). Three focus groups and five interviews (n = 31) included infrequent bus users from the survey to determine reasons for strategy preferences and potential impact on PA. Results: The top three strategies in the survey, with supporting rationale from qualitative data, were: provision of real‐time bus information ("…because I can better plan…"); bus‐only lanes ("…it just speeds the whole thing up…") and employee incentives/rewards for example bus fare credits ("…it really comes down to money…"). Full‐time students favoured cost‐saving strategies most and residents in outer suburbs favoured infrastructure‐based strategies most. Qualitative data indicated that potential for enhanced certainty, efficiency or cost‐savings drove strategy preferences and some strategies may lead to PA gain (eg through the location of Park and Ride facilities). Conclusions: Real‐time information, bus‐only lanes and employee incentives/rewards appear most promising for increasing bus use in this population, but tailoring strategies may be required. Discrete PT enhancement strategies may result in PA gain. So what?: Increasing PA through transport behaviour has been underexplored. The potential for PA gain through greater PT use and discrete PT use enhancement strategies is an important public health consideration. Summary: Public transport use can lead to physical activity (PA) gain. About 1091 adult Tasmanian survey respondents favoured three/ten strategies to increase bus use: real‐time bus information, bus‐only lanes and employee incentives/rewards. Follow‐up focus groups/interviews (n = 31) indicated: potential for better certainty, efficiency or cost‐savings drove strategy preferences; some strategies may facilitate PA gain.